Dynamic deformation image de-blurring and image processing for digital imaging correlation measurement. (November 2017) - Guo, X.; Li, Y.; Suo, T.; Liu, H.; Zhang, C.
Highlights: A method for de-blurring of images captured in the dynamic deformation is proposed. De-blurring is achieved based on the dynamic-based approach. The proposed method has been evaluated by using the Hopkinson bar loading system. Abstract: This paper proposes a method for de-blurring of images captured in the dynamic deformation of materials. De-blurring is achieved based on the dynamic-based approach, which is used to estimate the Point Spread Function (PSF) during the camera exposure window. The deconvolution process involving iterative matrix calculations of pixels, is then performed on the GPU to decrease the time cost. Compared to the Gauss method and the Lucy–Richardson method, it has the best result of the image restoration. The proposed method has been evaluated by using the Hopkinson bar loading system. In comparison to the blurry image, the proposed method has successfully restored the image. It is also demonstrated from image processing applications that the de-blurring method can improve the accuracy and the stability of the digital imaging correlation measurement.